Role of NGO in effective implementation of PFA and CEDAW in Bangladesh - Khan, Salma; NGO Coalition on Beijing Plus Five (Bangladesh) (Dhaka : NGO Coalition on Beijing Plus Five, 2003)
Contributed papers presented at various national level workshops and seminars.
English and Bengali.
Keywords: Women's rights -- Bangladesh -- Congresses; Sex discrimination against women -- Bangladesh -- Congresses; Women -- Bangladesh -- Social conditions -- Congresses; Social sciences